The decreased serum levels of interleukin-38 in patients with gout and its clinical significance - Huang, Hua; Zhou, Yinxin; Li, Yan; Zhao, Hui; Wu, Xiudi; Li, Mingcai (Frontiers in Immunology, 2024)
Background: Interleukin (IL)-38 is a newly discovered anti-inflammatory cytokine. However, its concentration and clinical significance in patients with gout remain unclear. This study aimed to investigate the levels of IL-38 in patients with gout and evaluate their clinical significance.Methods: Thirty-two patients with active gout, 27 patients with inactive gout, and 20 negative controls (NCs) were included in the study. Clinical parameters, including white blood cell count, Creactive protein, serum amyloid A, erythrocyte sedimentation rate, uric acid, urea, creatinine, alanine aminotransferase, aspartate aminotransferase, glutamyl transpeptidase, and glycoserated serum protein, were obtained from laboratory tests of blood samples. The serum concentration of IL-38 was determined using enzyme-linked immunosorbent assay. Spearman's correlation analysis and receiver operating characteristic curve assessments were used to investigate the role and diagnostic value of IL-38 in gout.Results: Patients with active and inactive gout exhibited significantly lower serum IL-38 levels than NCs. No significant differences were observed between the two gout groups. A negative correlation was observed between IL-38 and white blood cell counts, whereas a positive correlation was found between IL-38 and creatinine levels. Furthermore, IL-38, either alone or in combination with uric acid, demonstrated substantial diagnostic potential. The findings suggest that the decreased serum levels of IL-38 in patients with gout compared to that in NCs indicates that IL-38 may have immunomodulatory effects on gout inflammation and possesses clinical application value.